Traffic Signs Comprehension among Motorcyclists: The Effect of Sign Type and Sign Familiarity - Maulina, Dewi; Andini, Elsa; Tanri, Diza; Kamsanih, Noviopatra; Mazaya, Shabrina; Zhafirah, Tamara (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research aimed to examine the effect of sign types and sign familiarity on traffic sign comprehension. A mixed factorial design experiment involved manipulating two sign types (symbols vs symbols and text) and two sign familiarity (familiar vs unfamiliar) of a traffic sign, with sign familiarity as a within-subject factor. Previous studies had found a relationship between the lack of traffic sign comprehension and accident likelihood. However, there was still a lack of research examining the sign characteristics that influence sign comprehension among motorcyclists. Participants were 86 young riders aged 18 to 25 who had a minimum of three years of riding experience in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas. Participants were given warning signs; then, sign comprehension was measured using sign comprehension time and sign comprehension level. The results show that there is a significant effect of sign familiarity and interaction between sign types and sign familiarity on sign comprehension time. On the other hand, sign types, sign familiarity, and interaction between sign types and sign familiarity have a significant effect on sign comprehension level. The implication of the research is that sign familiarity and sign type must be taken into consideration in designing effective traffic signs, especially warning signs, to facilitate riders in understanding traffic signs more quickly and accurately.